2022
DOI: 10.20473/j.djmkg.v55.i4.p209-214
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 plasma levels and erythrocyte sedimentation rate on oral candidiasis animal model

Abstract: Background: A study with female animal models is important because the system immune of females is remarkably different from the male because of interaction between sex hormone and immune system. Interleukin-17 (IL-17) plays an important role in immune response toward Candida albicans (C. albicans) infection and Erythrocyte Sedimentation Rate (ERS) is an easy and sensitive test to assess the inflammation. Purpose: This study aimed to evaluate C. albicans infection, analyse the IL-17 levels and ESR in a female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The elevated erythrocyte sedimentation rate may indicate increased inflammation-sensitive plasma proteins (ISPs). 17 The results of this study proved that even IL-17 levels in the oral candidiasis rat model remained at a low level on the eighth day, but the mucosal immune response in the rat model increased. Even though IL-17 is the main cytokine of the body's defence against fungi, it is well known that cytokines in the body will work together synergistically in fighting infections, including fungal infections.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The elevated erythrocyte sedimentation rate may indicate increased inflammation-sensitive plasma proteins (ISPs). 17 The results of this study proved that even IL-17 levels in the oral candidiasis rat model remained at a low level on the eighth day, but the mucosal immune response in the rat model increased. Even though IL-17 is the main cytokine of the body's defence against fungi, it is well known that cytokines in the body will work together synergistically in fighting infections, including fungal infections.…”
Section: Discussionmentioning
confidence: 52%
“…15 The rat model of oral candidiasis we made in previous studies showed infection through microbiological and histopathological evaluations on the fifth and eighth day after C. albicans inoculation. 16 On day 8, there was a decrease in infection compared to day 5, but on analysis of the IL-17 plasma level, it remained lower than normal. 17 This is controversial because IL-17 is a key cytokine in the defence against fungal infections.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations